STUDIES ON THE ANATOMY AND HISTOLOGY OF THE FOREGUT IN ORCHESTIA PLATENSIS KRYER (CRUSTACEA : AMPHIPODA) - LALITHA, M.; SHYAMASUNDARI, K.; RAO, K. HANUMANTHA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1992)
The digestive tract of Orchestia platensis is a straight tube consisting of a foregut, midgut and hindgut. foregutis differentiated into oesophagus, cardiac stomach and pyloric stomach. The oesophagusandston are histologically similar; in each the wall consists of chitinous intima, columnar epithelium, tunica prop circular muscles and sometimes, longitudinal muscles. The wall of the cardiac and the pyloric stomac arranged in complicated folds forming a number of ampullae and lamellae. The cardiac stomach s elaborate gastric mill system forming a triturating apparatus. The posterior triangular pyloric stomach as a filtering apparatus.